Increased faecal shedding in SARS-CoV-2 variants BA.2.86 and JN.1 - Dhammika Leshan Wannigama; Mohan Amarasiri; Phatthranit Phattharapornjaroen; Cameron Hurst; Charin Modchang; Sudarat Chadsuthi; Suparinthon Anupong; Kazuhiko Miyanaga; Longzhu Cui; Stefan Fernandez; Angkana T. Huang; Puey Ounjai; et al. (2024)
The SARS-CoV-2 variant JN.1 swiftly became the global dominant strain1Yang S Yu Y Xu Y et al.Fast evolution of SARS-CoV-2 BA.2.86 to JN.1 under heavy immune pressure.Lancet Infect Dis. 2024; 24: e70-e72Summary Full Text Full Text PDF PubMed Scopus (18) Google Scholar, 2Wannigama DL Amarasiri M Phattharapornjaroen P et al.Tracing the new SARS-CoV-2 variant BA.2.86 in the community through wastewater surveillance in Bangkok, Thailand.Lancet Infect Dis. 2023; 23: e464-e466Summary Full Text Full Text PDF PubMed Scopus (11) Google Scholar due to a spike protein Leu455Ser substitution, boosting transmissibility and immune-escape capabilities, surpassing its predecessor BA.2.86 and other variants.1Yang S Yu Y Xu Y et al.Fast evolution of SARS-CoV-2 BA.2.86 to JN.1 under heavy immune pressure.Lancet Infect Dis. 2024; 24: e70-e72Summary Full Text Full Text PDF PubMed Scopus (18) Google Scholar, 3Qu P Xu K Faraone JN et al.Immune evasion, infectivity, and fusogenicity of SARS-CoV-2 BA.2.86 and FLip variants.Cell. 2024; 187: 585-595Summary Full Text Full Text PDF PubMed Scopus (7) Google Scholar, 4Kaku Y Okumura K Padilla-Blanco M et al.Virological characteristics of the SARS-CoV-2 JN.1 variant.Lancet Infect Dis. 2024; 24: e82Summary Full Text Full Text PDF PubMed Scopus (13) Google Scholar These alterations have resulted in a surge of COVID-19 cases, reflected in wastewater-surveillance data surpassing rates, observed during the initial omicron wave. However, concerns persist that JN.1 might have an increased capacity to replicate in the gut, potentially leading to infected individuals shedding a higher number of viral copies than previously seen. As there is currently a lack of available data for fecal viral shedding, we are presenting the initial longitudinal and quantitative faecal shedding data for SARS-CoV-2 RNA in individuals infected with XBB.1.5, EG.5.1, HV.1, JD.1.1, BA.2.86, and JN.1. 856 faecal samples were obtained from 113 non-hospitalised individuals with confirmed PCR positivity for SARS-CoV-2 RNA. Variants were identified through Sanger sequencing. Detailed protocols for processing and extracting SARS-CoV-2 RNA from stool samples are provided in the appendix (pp 6–9, 15–19). A summary of the cohort demographics is shown in the appendix (p 10). The cohort contained all individuals (n=113) fully vaccinated for SARS-CoV-2, with eight (7%) having received BA4/5 bivalent booster. The median number of samples collected per individual was eight, with a range of 4–12 samples per individual. A significant difference (p<0·0001) in faecal SARS-CoV-2 RNA concentration was observed among the variants XBB.1.5, EG.5.1, HV.1, JD.1.1, BA.2.86, and JN.1 on days 0, 3, 5, 7, 9, and 15 (figure). Specifically, BA.2.86 and JN.1 exhibited significant differences (p=0·0010) compared with XBB.1.5, EG.5.1, HV.1, and JD.1.1 across symptoms onset days 0, 3, 5, 7, 9, and 15 (figure; appendix p 11). Additionally, significant differences (p = 0·0010) were also noted between EG.5.1 and JD.1.1 or XBB.1.5. Furthermore, a similar significant difference (p=0·0010) between BA.2.86 and JN.1 was consistently observed on symptoms onset days 0, 3, 5, 7, 9, and 15. In nasopharyngeal samples, significant differences in SARS-CoV-2 RNA concentration were observed between JN.1 and BA.2.86 (p=0·0046), and HV.1 (p=0·0014) on day 0 post-PCR positivity. Moreover, on the same day, significant differences were noted between HV.1 and JD.1.1 (p=0·021) and XBB.1.5 (p=0·0056). Additionally, BA.2.86 and XBB.1.5 (p=0·039) displayed significant differences in SARS-CoV-2 RNA concentration on day 0. 37 (33%) individuals did not have symptoms of COVID-19. There were no significant differences in faecal shedding values between symptomatic and asymptomatic individuals on days 0 (p=0·072), 3 (p=0·97), 5 (p=0·061), 9 (p=0·5739), 11 (p=0·567), and 21 (p=0·65) relative to days since PCR positivity for SARS-CoV-2 RNA (figure). However, there was a significant difference in faecal shedding values between day 7 (p=0·0013) and day 15 (p=0·013). Body aches, cough, loss of appetite, chills, diarrhoea, sore throat, and nausea were very common among the JN.1-infected individuals compared with other variants (figure). There was no statistically significant difference in the prevalence of these symptoms among variants (appendix p 14). Symptoms were resolved within 4–5 days in 89% of individuals after symptom onset. 44 (39%) individuals exhibited presymptom onset faecal shedding of SARS-CoV-2 RNA, with stool samples collected 3 days before the onset of symptoms (figure). Taken together, we provide evidence confirming that both BA.2.86 and JN.1 show higher rates of viral shedding compared with XBB.1.5, EG.5.1, HV.1, and JD.1.1, including in presymptomatic and vaccinated individuals, which might partly explain the increase in wastewater levels. Although JN.1 is known for greater transmissibility and immune evasion,1Yang S Yu Y Xu Y et al.Fast evolution of SARS-CoV-2 BA.2.86 to JN.1 under heavy immune pressure.Lancet Infect Dis. 2024; 24: e70-e72Summary Full Text Full Text PDF PubMed Scopus (18) Google Scholar, 4Kaku Y Okumura K Padilla-Blanco M et al.Virological characteristics of the SARS-CoV-2 JN.1 variant.Lancet Infect Dis. 2024; 24: e82Summary Full Text Full Text PDF PubMed Scopus (13) Google Scholar none of our cohort had severe digestive illnesses from JN.1, although it might contribute to more efficient gut tissue infection. This assertion requires confirmation through comprehensive studies. Our findings provide crucial first insights into viral faecal shedding among individuals infected with BA.2.86 and JN.1 variants. This information could be valuable for the clinical and epidemiological management of SARS-CoV-2 as well as those practising wastewater-based epidemiology. For more on COVID-19 variant rates see https://gisaid.org/hcov19-variants For more on COVID-19 variant rates see https://gisaid.org/hcov19-variants MA and CH contributed equally as joint first authors. DLW, CH, and PH: conception, funding acquisition, investigation, data curation, formal analysis, supervision, and writing original draft of the manuscript. MA: conception, investigation, data curation, formal analysis, supervision, and writing original draft of the manuscript. CM: data curation, formal analysis, and supervision. SC and SA: formal analysis, critical review, and editing of the manuscript. PP, KM, LC, SF, ATH, PO, AS, NKDR, DS, TF, KSe, AL, TK, PGH, AN, AKi, RS, ST, AKh, and KSh: supervision, critical review, and editing of the manuscript. TC: critical review and editing of the manuscript. SA and HI: conception, funding acquisition, investigation, supervision, critical review, and editing of the manuscript. DLW was supported by Balvi Philanthropic Fund, Chulalongkorn University (Second Century Fund Postdoctoral Fellowship), University of Western Australia (Overseas Research Experience Fellowship), and Yamagata Prefectural Central Hospital (Clinical Residency Fellowship). CM was supported by the Centre of Excellence in Mathematics, Ministry of Higher Education, Science, Research and Innovation, Centre of Excellence on Medical Biotechnology, and Thailand Centre of Excellence in Physics. ATH is a Herchel Smith Postdoctoral Research Fellow. AKi is a Rothwell Family Fellow. The funders had no role in study design, collection, analysis, or interpretation of data, writing of the report, or in the decision to submit the article for publication. All other authors declare no competing interests. This study was conducted in accordance with the principles of the Declaration of Helsinki, Good Clinical Practice guidelines, and other applicable laws and regulations, including Strengthening the Reporting of Observational studies in Epidemiology guidelines. The study is part of the COVID-19 surveillance study and was reviewed and approved by the institutional review board at Yamagata Prefectural Central Hospital. All volunteers or their legally acceptable representatives provided written informed consent. We thank all the volunteers who kindly supported the sample collection and all the volunteer participants. We thank especially the LGBTQIA+ community in Yamagata for helping with the sample collection. We embrace inclusive, diverse, and equitable conduct of research. Our team comprises of individuals who self-identify as under-represented ethnic minorities, gender minorities, members of the LGBTQIA+ community, and individuals living with disabilities. We actively promote gender balance in our reference list while maintaining scientific relevance. Download .pdf (.6 MB) Help with pdf files Supplementary appendix